Spheroid mechanics and implications for cell invasion - Boot, Ruben C.; Koenderink, Gijsje H.; Boukany, Pouyan E. (Advances in physics: X, 2021)
Spheroids are widely used in vitro 3D multicellular model systems that mimic complex physiological microenvironments of tissues. As different cell types vary in deformability and adhesion, the choice of (heterogeneous) cell composition will define overall spheroid mechanics, including their viscoelasticity and effective surface tension. These mechanical parameters directly influence cell sorting and possibly cell invasion into the extracellular matrix. Spheroid models therefore provide fundamental insights in the relation between cellular mechanics and important physiological processes, such as tissue formation, embryonic tissue remodeling, and cancer metastasis. In this review, we first summarize and compare current biophysical tools that probe mechanics of spheroids either from the outside or from within, then relate spheroid mechanics to cell mechanics and cell-cell adhesion, and subsequently discuss the role of spheroid mechanics alongside surrounding microenvironment parameters in (cancer) cell migration. We conclude by pointing out the research gaps and drawing the attention to novel techniques that could shed more light on the biophysical characterization of spheroids in the framework of tissue remodeling and cancer metastasis.